A decision-making model to outsource complex product systems research and development projects - Hassan Torabi (goodwood publishing, 2022)
Purpose: Complex product systems are goods with high technology. Research and development on their production requires resources beyond the capability of an organization. This study aimed to propose a decision-making model to outsource CoPS R&D projects. Research methodology: The decision-making criteria were identified using the literature review and the Fuzzy Delphi method. Two conceptual models were developed using structural equation modeling. The pattern of relationships among criteria were determined by employing the DEMATEL technique. Then to prioritize the criteria and select between alternatives, the analytical network process was utilized. Results: In the intra-organizational model, “project characteristics” has a positive effect on “requirements” and the latter has a similar effect on “competency”. In the extra-organizational model, the “competency” has a positive effect on the “task performing capability”, and the latter has a similar effect on the “adaptability”. A two-stage decision model was developed. In the first stage, the decision to in/outsource the project is taken. In the second one, the mechanism of outsourcing is determined. Limitation: Due to the breadth of types of inter-organizational cooperation in the range of integration between the organization and the supplier, only one of these types, namely outsourcing, has been addressed. Contribution: An organization cannot outsource the development of CoPS unless it enjoys the technological, contractual, project control, integration, and soft technologies competencies. Furthermore, appropriate communication strategies and adequate financial resources are required. The managers of organizations developing CoPS such as airplanes, missiles, and power plants and can utilize the implications of the model.